Comment on “Emotional Intelligence and Resilience ‘PROGRAM’ Improves Wellbeing and Stress Management Skills in Preclinical Medical Students” [Letter] - Wardoyo S; Anwar T (Advances in Medical Education and Practice, 2023)
Slamet Wardoyo,1 Taufik Anwar2 1Department of Environmental Health, Poltekkes Kemenkes Surabaya, Surabaya, Indonesia; 2Department of Environmental Health, Poltekkes Kemenkes Pontianak, Pontinak, IndonesiaCorrespondence: Slamet Wardoyo, Tel +62 857 8754 9486, Email slaametwardoyo91@gmail.com